2019
DOI: 10.24198/sosiohumaniora.v21i3.21288
|View full text |Cite
|
Sign up to set email alerts
|

Karakteristik Petani Dan Profil Usahatani Ubi Jalar Di Kec. Arjasari, Kab. Bandung

Abstract: Ubi jalar merupakan salah satu sumberdaya hayati unggulan yang berdaya saing industri karena permintaan untuk ekspor yang tinggi. Namun demikian, kajian agribisnis ubi jalar dari sudut pandang sosial ekonomi di tingkat petaninya belum banyak diteliti. Penelitian ini bertujuan untuk: 1) Menganalisis karakteristik individu petani ubi jalar; dan 2) Memahami karakteristik usahatani ubi jalar ditinjau dari penggunaan benih ubi jalar, status kepemilikan lahan, pola tanam ubi jalar, penggunaan pupuk dan pestisida ser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
9

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 3 publications
1
8
0
9
Order By: Relevance
“…In other words, farmers gain on each invested IDR, 0.105 IDR that is a bit more than the capital they have invested in the production of this crop. The results tally with those of other researchers obtained for sweet potato farming in other locations in Indonesia like Ampek Angkek in Agam regency (benefit-cost ratio 0.86) [6] and in Reban, Batang regency with the highest revenuecost ratio 1.38 [7], but lower than that of in Arjasari, Bandung regency with benefit-cost ratio 1.24 [8] and in Pati, Jember regency (benefit-cost ratio 1.88) [9]. In other words, the production of sweet potato in Gunung Talang region is financially more profitable than that of in Ampek Angkek and Reban but less profitable than that of in Arjasari and Pati.…”
Section: Advances In Biological Sciences Research Volume 13supporting
confidence: 86%
See 3 more Smart Citations
“…In other words, farmers gain on each invested IDR, 0.105 IDR that is a bit more than the capital they have invested in the production of this crop. The results tally with those of other researchers obtained for sweet potato farming in other locations in Indonesia like Ampek Angkek in Agam regency (benefit-cost ratio 0.86) [6] and in Reban, Batang regency with the highest revenuecost ratio 1.38 [7], but lower than that of in Arjasari, Bandung regency with benefit-cost ratio 1.24 [8] and in Pati, Jember regency (benefit-cost ratio 1.88) [9]. In other words, the production of sweet potato in Gunung Talang region is financially more profitable than that of in Ampek Angkek and Reban but less profitable than that of in Arjasari and Pati.…”
Section: Advances In Biological Sciences Research Volume 13supporting
confidence: 86%
“…Factors affected the sweet potato's production in Ampek Angkek were seeds, organic fertilizer, labor in the family, and labor outside the family. In Anjarsari, West Java, Indonesia, R/C ratio of sweet potato farming also showed that sweet potato was feasible to cultivate, although 25% of its cost was for planting materials [8]. The feasibility of sweet potato farming was also mentioned by Chasanah et al [7].…”
Section: Feasibility Of Sweet Potato Farmingmentioning
confidence: 99%
See 2 more Smart Citations
“…Farmer characteristics are personal data owned by farmers or characteristics inherent in individual farmers that can distinguish with other farmers. According to Hapsari et al (2019), despite being in the same residential and cultural environment, the characteristics of each farmer are very diverse, known from the age group of the head of the family, the level of education of the head of the family, the main profession of the family and the extent of land ownership.…”
Section: Characteristics Of Mango Farmersmentioning
confidence: 99%